Data Security and Data Protection in Cloud Privacy Systems - Harson Kapoh; Putri Aprilyana; Yeremia Sumampow; Marsya Mailake; Farel Manimpurung; Hafizhan Pakaya (Syntax Corporation Indonesia, 2024)
In this modern world, the internet has become very influential in our daily lives. The Internet has many uses to solve various problems, one of which is full hardware storage, therefore the Internet provides software-based data, for example, cloud storage applications. The study aims to analyze and evaluate various data security techniques and protection methods used in the cloud computing framework, focusing on vulnerability identification, risk mitigation strategy assessment, and user security awareness improvement. In addition, this study aims to analyze data security techniques and data protection approaches applied to cloud systems. In addition, the study also assesses potential risks and mitigates security threats such as cyberattacks and data breaches. Using qualitative methodologies, the study investigated relevant literature, examined real-life cases of data breaches, and analyzed the effectiveness of security measures such as encryption and multi-factor authentication. The findings show that cloud systems remain vulnerable to cyber threats like DDoS attacks, credential theft, and data breaches due to inadequate security protocols. Key recommendations include adopting encryption, improved multi-factor authentication practices, and encouraging collaboration between cloud service providers and users to strengthen data security. The research contributes by proposing a comprehensive approach to improving data protection in cloud environments, ensuring a secure and resilient infrastructure for users. Implementing these findings will support the development of more secure cloud technologies and increase user confidence in data security practices. It is hoped that the study's results can provide recommendations to improve data security and data protection in cloud systems.